Análisis financiero a la cooperativa de ahorro y crédito inti wasi ltda., inticoop del cantón Saraguro durante los periodos 2019 – 2020 y la incidencia del covid-19 en el rendimiento financiero. - Morocho Sigcho, Sonia Esperanza (2022)
The Curriculum Integration or Degree Work called FINANCIAL ANALYSIS OF THE COOPERATIVA DE AHORRO Y CRÉDITO "INTI WASI" LTDA., INTICOOP, OF SARAGURO CANTON DURING THE PERIODS 2019 - 2020 AND THE IMPACT OF COVID-19 ON FINANCIAL PERFORMANCE, was developed from the problem found in the cooperativa related to the lack of applying methods of financial analysis. To comply with the objectives, the application of horizontal and vertical analysis was developed, which allowed knowing the economic and financial position of the cooperative through the information presented in the financial statements, evidencing the existing variations from one period to another, reflecting that the most representative variation within the assets is the loan portfolio with a value of $918,581.2, equivalent to 71.59% for the year 2019 and $1,221,587.44 equivalent to 87.96% for the year 2020, within the liabilities It is evident that it is mostly represented by current liabilities with a value of $802,092.07 equivalent to 62.90% for the year 2019 while for 2020 it reflects $879,470.04 produced by demand deposits and time deposits; situation that shows that the cooperative is fulfilling its institutional mission by providing services in the different credit portfolios . In addition, financial indicators required by Superintendencia de Economía Popular y Solidaria were applied, the same ones that allowed measuring the economic and financial situation. Determining that the cooperative presents excellent levels of liquidity with 93.46% and 52.51% in the years 2019 and 2020 respectively. It also shows late-payment levels below the standard, comprising 4.92% in 2019 and 2.38% in 2020, thus concluding that the cooperative had a beneficial decrease in its levels of late-payment as a result of the increase in the value of the loan portfolio. Finally, the financial analysis report was prepared, containing results that allow evidence of the existing changes from one period to another, as well as the strong variations produced by the health crisis caused by Covid- 19, allowing the development of conclusions and recommendations that help the managers of cooperative to make better decisions based on the results of this analysis.